ANALISIS RETURN SAHAM LQ45 DI BURSA EFEK INDONESIA - Cindy Putri Cahyani (2021)
This research is a quantitative study which aims to determine the effect of systematic risk and trading frequency on LQ45 company stock returns on the Indonesia Stock Exchange for the period 2016 to July 2020. The sampling technique used was purposive sampling with the criteria that the company was included in the LQ45 index consecutively during the observation period and obtained a sample of 31 companies. The research data analysis technique used panel data regression analysis with the E-views 11 program and a significance level of 5%. The results of this study indicate that partially systematic risk variables as measured by beta have an effect on stock returns, while trading frequency has no effect on LQ45 stock returns on the Indonesia Stock Exchange for the period 2016 to July 2020.